The Arabidopsis Sin3-HDAC Complex Facilitates Temporal Histone Deacetylation at the CCA1 and PRR9 Loci for Robust Circadian Oscillation - Lee, Hong Gil; Hong, Cheljong; Seo, Pil Joon (Frontiers in Plant Science, 2019)
The circadian clock synchronizes endogenous rhythmic processes with environmental cycles and maximizes plant fitness. Multiple regulatory layers shape circadian oscillation, and chromatin modification is emerging as an important scheme for precise circadian waveforms. Here, we report the role of an evolutionarily conserved Sin3-histone deacetylase complex (HDAC) in circadian oscillation in Arabidopsis. SAP30 FUNCTION-RELATED 1 (AFR1) and AFR2, which are key components of Sin3-HDAC complex, are circadianly-regulated and possibly facilitate the temporal formation of the Arabidopsis Sin3-HDAC complex at dusk. The evening-expressed AFR proteins bind directly to the CIRCADIAN CLOCK ASSOCIATED 1 (CCA1) and PSEUDO-RESPONSE REGULATOR 9 (PRR9) promoters and catalyze histone 3 (H3) deacetylation at the cognate regions to repress expression, allowing the declining phase of their expression at dusk. In support, the CCA1 and PRR9 genes were de-repressed around dusk in the afr1-1afr2-1 double mutant. These findings indicate that periodic histone deacetylation at the morning genes by the Sin3-HDAC complex contributes to robust circadian maintenance in higher plants.